1166 Performance of the Definitions of the Systemic Inflammatory Response Syndrome and Sepsis in Newborns. (October 2012) - Hofer, N; Mueller, W; Resch, B
Abstract : Background and Aims: In 2002 the International Pediatric Sepsis Consensus Conference created definitions for the systemic inflammatory response syndrome (SIRS) and sepsis adoptable for paediatric patients. We aimed to examine the applicability of the pediatric definitions of SIRS and sepsis to newborns in the diagnosis of early (EOS) and late onset sepsis (LOS). Methods: Retrospective cohort study including 1. all term newborns hospitalized within the first 24 hours of life and 2. all infants with episodes of suspected LOS with a corrected gestational age of >37 weeks at onset of LOS from 2004 to 2008. Results: Thirteen of 245 newborns included had culture proven EOS (5%) and 5 newborns had culture proven LOS. SIRS and sepsis criteria applied to 38% of EOS positive infants and to 100% of LOS positive infants. The two major diagnostic criteria white blood cell count and fever/hypothermia, of which at least one has to apply for fulfilling SIRS and sepsis criteria, had a sensitivity of 15% and 38% in diagnosis of EOS and of 100% and 80% in diagnosis of LOS, respectively. Conclusions: The definitions of SIRS and sepsis applied to all cases of culture proven LOS. However, the single diagnostic criteria were insensitive in diagnosis of culture proven EOS with thus wrong classification of more than 60% of all cases. An evidence based approach to find the appropriate criteria for defining EOS in newborns is needed.